Scar endometriosis: pre-operative diagnosis by fine needle aspiration cytology - Chavarkar, Sneha P.; Rao, Rajiv; Pandey, Akanksha; Khatu, Shirish P. (International Journal of Research in Medical Sciences, 2019)
Scar endometriosis is a rare entity commonly observed after obstetrical and gynaecological procedures. The diagnosis is often delayed due to the non-specific nature of symptoms. Detailed clinical history of cyclical pain, location in proximity to a surgical scar and a suspicion of this rare entity in women of childbearing age are key to preoperative diagnosis. This is a case of a patient who presented with a troublesome scar after Caesarean section. On Fine needle aspiration cytology (FNAC) a diagnosis of scar endometriosis was provided which was further confirmed on histopathology. Herein we discuss the cytomorphological features of this rare entity and also emphasize the importance of its diagnosis on FNAC which is a rapid and cost-effective method.